Analisis Keberlanjutan Kawasan Usaha Perkebunan Kopi (KUPK) Rakyat di Desa Sidomulyo Kabupaten Jember - Elida Novita; I B Suryaningrat; Idah Andriyani; Sukrisno Widyotomo (Faculty of Agricultural Technology, Universitas Gadjah Mada, Yogyakarta, Indonesia, 2012)
Sidomulyo village, Silo region is one of main small holder coffee producer at Jember district. Unpredictable world production and price can cause unsustainability of small holder coffee production. The research objective was to evaluate sustainability of small holder coffee plantation in Sidomulyo, Jember district. Based on purposive and random sampling survey, questionnaire and discussion with key persons were implemented in this research in collecting data. Dimension of ecology, social institutional, economic and technology were analyzed using Rap-Coffee program modified from Rapfi sh software. The result reveals that from four dimensions implemented in this research, the sustainability index was 59,5 % means that activity of small holder coffee plantation at Sidomulyo still have sustainability as a coffee production unit. This index could be increased through factors improvement of each dimension. The improvement of high sensitivity attributes in each dimension is strongly needed to develop better regulation to support the continuity of small holder plantation of coffee production unit at Sidomulyo.ABSTRAKDesa Sidomulyo, Kecamatan Silo merupakan salah satu sentra produksi kopi rakyat utama di Kabupaten Jember. Perkembangan produksi dan harga kopi dunia yang tidak pasti dapat berimplikasi terhadap keberlanjutan usaha pertanian kopi rakyat. Tujuan penelitian ini adalah untuk mengevaluasi keberlanjutan usaha kopi rakyat di Desa Sidomulyo, Kabupaten Jember. Berdasarkan purposive and random sampling survey, penelitian ini menggunakan kuesioner dan diskusi dengan pihak terkait dalam pengambilan data. Dimensi ekologi, sosial kelembagaan, ekonomi dan teknologi dianalisis dengan menggunakan program Rap-Coffee hasil modifi kasi dari program Rapfi sh. Berdasarkan simulasi program Rap-Coffee untuk keempat dimensi keberlanjutan, maka Indeks Keberlanjutan KUPK Desa Sidomulyo adalah 59,5 % yang berarti berlanjut. Indeks keberlanjutan ini dapat ditingkatkan melalui perbaikan terhadap faktor pengungkit (indikator sensitif). Oleh karena itu di dalam perencanaan kebijakan untuk pengembangan KUPK Desa Sidomulyo sebaiknya memprioritaskan pada peningkatan indikator yang memiliki sensitivitas tinggi di masing-masing dimensi.